2009
DOI: 10.3198/jpr2008.04.0215crc
|View full text |Cite
|
Sign up to set email alerts
|

‘Vavilov II’, a New Siberian Wheatgrass Cultivar with Improved Persistence and Establishment on Rangelands

Abstract: ‘Vavilov II’ Siberian wheatgrass [Agropyron fragile (Roth) Candargy] (Reg. No. CV‐30, PI 653686) was released by the USDA‐ARS, the U.S. Army‐Engineer Research and Development Center, Utah Agricultural Experiment Station, and the USDA‐NRCS. Vavilov II was developed for reseeding sandy soils on disturbed rangelands dominated by annual weeds as a result of severe disturbance, frequent fires, and soil erosion. Selection emphasis in Vavilov II was on seedling establishment and stand persistence. During the establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…The latter accessions were classified as A. fragile var. sibiricum (Jensen et al, 2000) and used in the development of Vavilov II (Jensen et al, 2009).…”
Section: Breeding Historymentioning
confidence: 99%
See 3 more Smart Citations
“…The latter accessions were classified as A. fragile var. sibiricum (Jensen et al, 2000) and used in the development of Vavilov II (Jensen et al, 2009).…”
Section: Breeding Historymentioning
confidence: 99%
“…It appears that genetic introgression has occurred between Siberian and standard forms in nature. This introgression is evident in the Siberian cultivars P-27, Vavilov, and Vavilov II by the morphological cline that exists between the long, narrow spike of Siberian wheatgrass and the shorter, wider spike of the standard forms of crested wheatgrass (Asay et al, 1995;Jensen et al, 2009). When combined across locations (Nephi and Blue Creek, UT), significant differences were observed for plant height, flag-leaf height, spike length, spike width, first lemma length, and first lemma awn length, all of these differentiating Stabilizer from Vavilov II and Vavilov (Table 2).…”
Section: Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“… 'CD-II' crested wheatgrass cultivar, currently on the market for purchase (Asay et al 1997)  RWR-Tetra-1 Tetraploid wildrye, a source-identified germplasm (Jensen et al 1998)  'Bozoisky-II' Russian wildrye cultivar )  'Vavilov II' Siberian wheatgrass cultivar (Jensen et al 2009) …”
Section: Introductionmentioning
confidence: 99%